Conductive Adhesive and Antibacterial Zwitterionic Hydrogel Dressing for Therapy of Full-Thickness Skin Wounds - Wang, Feng; Wang, Shuguang; Nan, Liping; Lu, Jiawei; Zhu, Ziqi; Yang, Jintao; Zhang, Dong; Liu, Junjian; Zhao, Xiao; Wu, Desheng (Frontiers in Bioengineering and Biotechnology, 2022)
Any sort of wound injury leads to the destruction of skin integrity and wound formation, causing millions of deaths every year and accounting for 10% of death rate insight into various diseases. The ideal biological wound dressings are expected to possess extraordinary mechanical characterization, cytocompatibility, adhesive properties, antibacterial properties, and conductivity of endogenous electric current to enhance the wound healing process. Recent studies have demonstrated that biomedical hydrogels can be used as typical wound dressings to accelerate the whole healing process due to them having a similar composition structure to skin, but they are also limited by ideal biocompatibility and stable mechanical properties. To extend the number of practical candidates in the field of wound healing, we designed a new structural zwitterion poly[3-(dimethyl(4-vinylbenzyl) ammonium) propyl sulfonate] (SVBA) into a poly-acrylamide network, with remarkable mechanical properties, stable rheological property, effective antibacterial properties, strong adsorption, high penetrability, and good electroactive properties. Both in vivo and in vitro evidence indicates biocompatibility, and strong healing efficiency, indicating that poly (AAm-co-SVBA) (PAS) hydrogels as new wound healing candidates with biomedical applications.